Active Perturbations Around Estimated Future Inputs in Modifier Adaptation to Cope with Measurement Delays⁎. Issue 18 (2018) - Gottu Mukkula, Anwesh Reddy; Wenzel, Simon; Engell, Sebastian
Abstract: The earlier the plant measurements are available for a given plant input, the quicker iterative real-time optimization by modifier adaptation (MA) can steer the plant to its optimum. In practical applications, in addition to the time required for a plant to reach its steady state and to the time a sensor needs to perform the measurement, further delays can occur. For example, due to the time required for the sample to reach the location of the sensor, caused by a remote positioning of the measurement device. We propose a modifier adaptation strategy where additional plant perturbations are performed around an estimate of the solution to the adapted optimization problem during the waiting period which is caused by the measurement delay. The strategy is tested on the benchmark Otto-Williams reactor case study and its performance is studied.